Creation of State Antibiogram and Subsequent Launch of Public Health–Coordinated Antibiotic Stewardship in New Hampshire: Small State, Big Collaboration. (January 2022) - Leeman, Hannah M.; Chan, Benjamin P.; Zimmermann, Carly R.; Talbot, Elizabeth A.; Calderwood, Michael S.; Dave, Apara R.; Santos, Paul; Hansen, Katrina E.
Background: An antibiogram is a summary of antibiotic susceptibility patterns for selected bacterial pathogens and antibiotics. The New Hampshire Department of Health and Human Services' Division of Public Health Services (DPHS) sought to create an annual state antibiogram to monitor statewide antibiotic resistance trends, guide appropriate empiric antibiotic prescribing, and inform future statewide antibiotic stewardship. Methods: Through legislative authority, DPHS required hospital laboratories to report antibiogram data annually. DPHS convened an advisory group of infectious disease and pharmacy stakeholders and experts to develop a standardized reporting form for bacteria and antibiotic susceptibility, which was disseminated to all 26 hospitals in New Hampshire. We combined the reported data into a statewide antibiogram, and we created clinical messaging to highlight findings and promote rational antibiotic prescribing among health care providers. Results: All hospital laboratories in New Hampshire submitted annual antibiogram data for 2016 and 2017, including more than 30 000 and 20 000 bacterial isolates recovered from urine and nonurine cultures, respectively, each year. The advisory group created clinical messages for appropriate treatment of common infectious syndromes, including uncomplicated urinary tract infections, community-acquired pneumonia, skin and soft-tissue infections, intra-abdominal infections, and health care–associated gram-negative aerobic infections. The statewide antibiograms and clinical messaging were widely disseminated. Conclusions: The small size of New Hampshire, a centralized public health structure, and close working relationships with hospitals and clinical partners allowed for efficient creation and dissemination of an annual statewide antibiogram, which has fostered public health–clinical partnerships and built a foundation for future state-coordinated antibiotic stewardship. This process serves as a model for other jurisdictions that are considering antibiogram development.